PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA ANTARA MODEL PEMBELAJARAN TARI BAMBU DENGAN MODEL PEMBELAJARAN TWO STAY TWO STRAY (Studi pada Pokok Bahasan Program Linear) - Rivo Panji Yudha (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
The purpose of this research is to know the result of student learning with bamboo dance learning model with TSTS learning model. And to know the significant difference between bamboo dance learning model with TSTS learning model on linear program subject. Sampling using group sampling technique or cluster sample, so that in can research in class XI PM I and XI PM 3, this consideration based on teacher SMK Wahidin Cirebon. After the data obtained then we analyze using the normality test and homogeneity test while the hypothesis test is t test. Learning outcomes using the Bamboo dance learning model are better than those using TSTS learning models. This can be seen from the average gain results using bamboo dance, averaging 72,33 higher than that using bamboo dance learning model with the average gain is 58,73